THE EFFECT OF AGGRESSIVE ENVIRONMENT ON THE DURABILITY OF CONCRETE STRUCTURES - Konoval, V. M. (Science and Transport Progress, 2005)
The article considers the issues of aggressive media influence upon corrosion-resistance and service lifespan of the collectors made up from reinforced concrete pipes. As the basic method of protection from internal corrosion it is suggested making obligatory tests of fillers on the effect of aggressive acids and alkalis.